Recent Advances in Immunotherapy for the Treatment of Malignant Melanoma - Tuli, Hardeep S.; Sak, Katrin; Iqubal, Ashif; Choudhary, Renuka; Adhikary, Shubham; Kaur, Ginpreet; Kumar, Pawan; Garg, Vivek Kumar (Current Pharmaceutical Design, 2022)
Malignant melanoma is one of the most worrisome malignancies due to its fast dissemination and early formation of metastases in multiple sites throughout the body. Despite the intensive efforts made in the last decades, the use of standard therapeutic strategies, including chemotherapy and radiotherapy, has not led to a substantial improvement in clinical outcomes, mainly because of the intrinsic resistance of melanomas to these treatment modalities. Therefore, in recent years, numerous studies have focused on the possibility of boosting the clinical responses of melanoma patients by using novel immunotherapeutic agents. In this review article, a comprehensive survey is presented about the approved immunotherapeutic drugs and their action mechanisms, besides describing the agents that are currently still in clinical trials. Moreover, the combination of immunotherapeutic drugs with conventional approaches, i.e., radiotherapy, chemotherapy, and targeted therapy, is another focal point of this review, providing valuable input for further elaboration of the best treatment regimens to prolong survival and improve the quality of life of melanoma patients.
Keywords: immunotherapy